The reasons of love - Frankfurt, Harry G., 1929-2023 (Princeton University Press, 2006)
This beautifully written book by one of the world's leading moral philosophers argues that the key to a fulfilled life is to pursue wholeheartedly what one cares about, that love is the most authoritative form of caring, and that the purest form of love is, in a complicated way, self-love. Harry Frankfurt writes that it is through caring that we infuse the world with meaning. Caring provides us with stable ambitions and concerns; it shapes the framework of aims and interests within which we lead our lives. The most basic and essential question for a person to raise about the conduct of his or.
Keywords: Liebe, ...; Practical reason.; Love.; Love; Raison pratique.; Amour.; love (emotion); FAMILY & RELATIONSHIPS -- Interpersonal Relations.; PHILOSOPHY -- Ethics & Moral Philosophy.; Practical reason; Praktische Vernunft; Ethik; Selbstliebe; Liefde.